Strategi Kebijakan Pembiayaan Pendidikan Untuk Mencapai Sasaran Kinerja Perguruan Tinggi Keagamaan Islam Negeri (Studi Kasus Pada UIN Sunan Kalijaga) - Rahayu, Yayuk Sri (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2024)
National education funding is prepared with reference to applicable laws and regulations, government policies, education development programs and their targets, and program implementation in the dimensions of space and time. In the implementation of education programs, various resource limitations will be faced, both in terms of facilities and infrastructure, manpower, and education budgets, both from the APBN and other sources. Therefore, a financing strategy is prepared to overcome these resource limitations so that the implementation of education programs can contribute significantly to the achievement of national education goals as mandated by Law Number 20 of 2003. The purpose of this study is to analyze and criticize: 1) The amount of education financing budget at PTKIN; 2) Education financing policy at PTKIN and; 3) Education Financing Policy Strategy in an effort to achieve Performance Targets at UIN Sunan Kalijaga. The results of the study indicate that 1). The amount of education financing allocation at PTKIN is not fully in line with the amendments to the 1945 Constitution; 2). The budget policy is implemented proportionally according to the needs and developments of each PTKIN; 3). The Education Financing Policy Strategy in an effort to achieve Performance Targets at UIN Sunan Kalijaga, overall, the achievement of performance indicator targets each year is still not optimal because there are several strategic targets that cannot be achieved even though other strategic targets have exceeded the targets set.